PERANCANGAN DAN PEMBUATAN CHARGE PHONE MENGGUNAKAN SOLAR CELL UNTUK DIGUNAKAN PADA FASILITAS UMUM OUTDOOR - Sonny Rumalutur (LPPM Poltek ST Paul, 2022)
In public facilities with open or outdoor types that are often visited, it is very difficult to find charging places such as cellphones, tablets, powerbanks and so on. The purpose of this final project is to produce a device that can charge mobile phone batteries to be used in public facilities that are outdoor with a source of electricity used from solar power. In a design and manufacture of charge phones using solar cells for use in outdoor public facilities, it is expected to be able to charge cellphone batteries in a short time and without problems. This solar cell phone charging device is designed for needs in public facilities such as bus stops, parks, beaches, football fields or in public facilities that are not accessible by PLN. Where users can directly charge the cellphone battery. Lack of resources in the Sun, so if the weather is cloudy then charging the storage battery is less than optimal. In accordance with the above problems that storage batteries are not able to last long with the capacity that is only used at this time. So there needs to be a maintenance step, which is to always control the battery water to keep it durable because storage batteries cannot last long.